The Effect Of Anterior Posterior Glide Mobilization Technique And Hold Relax On Functional Activities In Frozen Shoulder Patients In The Physiotherapy Clinic Grandmed Hospital Lubuk Pakam - Rizka Mutiara; Rabiatun Nasution (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: The American Shoulder and Elbow Surgeons defines frozen shoulder as a condition with a specific cause characterized by limited active and passive movement of the shoulder joint due to damage to internal tissues. Physiotherapy modalities that can be applied to this condition include anterior-posterior glide mobilization and hold relax techniques. Objective: This study was to analyze the effect of administering Anterior Posterior Glide Mobilization and Hold Relax on patients with frozen shoulder. Method: Using a quasi-experimental design with two treatment groups and pre-test and post-test measurements, involving 14 respondents. Functional activity assessment was carried out using the SPADI instrument, while data analysis used paired t-test and independent t-test. Results: The study showed a significant difference between the two types of treatment. Conclusion: The administration of Anterior Posterior Glide Mobilization and Hold Relax had a positive effect on increasing functional activity in frozen shoulder patients. Suggestions for future research are expected to involve a larger sample size and a longer intervention duration to obtain more optimal results.